WHY GRANDPARENTS TELL STORIES: INTRODUCING THE INTERGENERATIONAL STORYTELLING FUNCTIONS QUESTIONNAIRE. (16th November 2018) - Weststrate, N; Glueck, J; Ferrari, M; Draxl, J; Stern, E
Abstract: Intergenerational storytelling between grandparents and their grandchildren is a developmentally meaningful and mutually enjoyable shared activity. Until now, we know little about grandparents' motivations for telling stories to younger generations. Do grandparents tell stories to entertain, to teach life lessons, or to simply pass the time? To cast light on this issue, we systematically investigated grandparents' reasons, and grandchildren's perceptions of their grandparents' reasons, for intergenerational storytelling. We asked samples of grandchildren and grandparents in Canada and Austria to complete the newly developed 61-item Intergenerational Storytelling Functions Questionnaire (ISFQ) that measures 12 potential reasons for storytelling. A preliminary factor analysis of the ISFQ, presented here for the first time, suggests that the 12 hypothesized reasons reduce to five factors. Listed in the order of their reported frequency, the factors have been labelled: positive reminiscence function, intimacy/entertainment function, wisdom/teaching function, familial/cultural heritage function, and passing-time function. To supplement these analyses, before completing the ISFQ, grandchildren and grandparents were asked to provide up to four open-ended reasons for intergenerational storytelling. A qualitative analysis of their responses indicates that we failed to capture one additional functional with the ISFQ. We have called this the negative reminiscence or 'processing the past' function, in which grandparents tell stories of negative life experiences (a common example being war stories) many years later in order to make sense of the experience in the present. We hope these preliminary results spark interest in studying the underlying motivations for intergenerational storytelling, for which we provide a new measurement tool.